PENGARUH KOMPETENSI KOMITE AUDIT, KEPEMILIKAN MANAJEMEN DAN UKURAN DEWAN KOMISARIS TERHADAP KUALITAS LAPORAN KEUANGAN - WAHDAN ARUM INAWATI; MUHAMAD MUSLIH; KURNIA KURNIA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This research aims to determine the influence of audit committee competency, managerial ownership, and size board of financial statements quality. Financial statement quality in this research measured by relevance. The research method applied quantitative causality method. The object of research is the food and beverage subsector companies listed on Indonesia Stock Exchange in period 2015 – 2018. The sample of this research which complied 8 samples with period of 4 years, so the data processed 32 data. The result of this research 62.1% independent variables can explain the quality of financial statements, while 37.9% is explained by other variables not included in this research. The audit committee competency variables, management ownership and the size of the board of commissioners have a simultaneous influence on the quality of financial statements. The audit committee competency variable has a negative effect while the size of the board of commissioners has a positive effect on the quality of financial statements partially. While management ownership has no influence on the quality of financial statements.